POSISI MANAJEMEN KURIKULUM DAN PEMBELAJARAN DALAM PENDIDIKAN - Aldo Redho Syam (Universitas Muhammadiyah Ponorogo, 2017)
The curriculum and learning have a very central position (importance) in education. Curriculum as written material or educational program (ideal curriculum) with more emphasis on operational learning process (real curriculum). The curriculum is related to the content/material that must be learned while the learning is related to the way to learn it. Without the curriculum as a plan, then learning will not be effective, and vice versa without learning as the implementation of a plan, the curriculum will have no meaning what. The curriculum aims as a direction, guidance, or assigns in the implementation of the learning process ). The curriculum directs all forms of learning activities for the achievement of educational goals.Thus, the curriculum and learning is an absolute requirement in a series of activities of educational institutions. What if there is no curriculum and lesson in school? In this case it is seen that the position of curriculum and learning is very central in the implementation of educational objectives, so that if there is no curriculum then the learning will not achieve the goal well, because in the curriculum contains the educational plan as a guide and also as a source of guidance in the implementation of learning field for educational institutions.